Neurofibromatosis: Molecular Pathogenesis and Natural Compounds as Potential Treatments - Amaravathi, Anusha; Oblinger, Janet L.; Welling, D. Bradley; Kinghorn, A. Douglas; Chang, Long-Sheng (Frontiers in Oncology, 2021)
The neurofibromatosis syndromes, including NF1, NF2, and schwannomatosis, are tumor suppressor syndromes characterized by multiple nervous system tumors, particularly Schwann cell neoplasms. NF-related tumors are mainly treated by surgery, and some of them have been treated by but are refractory to conventional chemotherapy. Recent advances in molecular genetics and genomics alongside the development of multiple animal models have provided a better understanding of NF tumor biology and facilitated target identification and therapeutic evaluation. Many targeted therapies have been evaluated in preclinical models and patients with limited success. One major advance is the FDA approval of the MEK inhibitor selumetinib for the treatment of NF1-associated plexiform neurofibroma. Due to their anti-neoplastic, antioxidant, and anti-inflammatory properties, selected natural compounds could be useful as a primary therapy or as an adjuvant therapy prior to or following surgery and/or radiation for patients with tumor predisposition syndromes, as patients often take them as dietary supplements and for health enhancement purposes. Here we review the natural compounds that have been evaluated in NF models. Some have demonstrated potent anti-tumor effects and may become viable treatments in the future.